40 Life stories by Qulutanguaq Jeremiassen (part 4.1) - Leonard, Stephen Pax (2011)
This is the first part of the fourth in a series of recordings, documenting the life of Qulutanguaq Jeremiassen. Qulutanguaq is the oldest member of the community (88 years old) and is considered the best living story-teller in the region. Qulutanguaq continues to tell the story of his life as a hunter .wav and .mp3 audio file